Influence of the suppression of the corner column on the compressive stresses of L-shaped RC shear walls - Merabti, Salem (Brazilian Journal of Production Engineering, 2024)
Designing innovative, economical, and earthquake-resistant structures is a major concern for civil engineers. In this article, a comparison is made between the performance of columns in L-shaped shear walls in three different buildings subjected to a strong earthquake. Additionally, shear walls with centered openings of different sizes were also studied. The impact of column removal and opening size on compressive stresses was examined. The results revealed that the influence of column removal from the L-shaped shear wall on the compressive stress response during a high earthquake was relatively minor for the four-story building. However, the influence was significant for the seven- and eleven-story buildings, which were affected by the shear wall thickness and the percentage of opening. Specifically, when the eleven-story buildings are braced with 15-cm thick walls, the compressive stress difference reaches a value of 5.40 MPa. This stress difference becomes noticeable at an opening percentage of 30%.